'We're not gonna have a big quit if loose ones are around': urban, African American smokers' beliefs concerning single cigarette use reduction. Issue 4 (6th August 2021) - Phan, Lilianna; Kuo, Charlene Chao-Li; Fryer, Craig S; Smith-Bynum, Mia A; Clark, Pamela I; Butler, James
Abstract: Single cigarette use (i.e. loosies, loose ones, singles) poses risks for smoking continuation among urban, African American smokers. There is, however, limited research to inform health education interventions addressing this behavior. We conducted 25 in-depth interviews with urban, African American users (ages 20–58 years) from Baltimore, MD and the District of Columbia in June and July 2018 to assess their beliefs about reducing single cigarette use. Interviews were guided by the Health Belief Model and its constructs of perceived benefits, perceived barriers, perceived susceptibility, perceived severity and self-efficacy. We analyzed qualitative data using framework analysis. Perceived benefits of reducing single cigarette use involved the avoidance of health risks, including concerns about buying fake cigarettes and exposure to unknown personal hygiene practices from sellers. Perceived barriers were the convenience of buying singles due to their availability, accessibility and low cost. Participants shared they were willing to use cognitive behavioral strategies to reduce their purchasing and use of singles. This study provides insights on potential intervention targets related to beliefs towards reducing single cigarette use. These findings can inform enforcement policies and health education interventions targeting single cigarette use among urban, African American smokers who use singles.